Heparin treatment increases thioredoxin interacting protein expression in hepatocellular carcinoma cells. (August 2015) - Gunes, Aysim; Iscan, Evin; Topel, Hande; Avci, Sanem Tercan; Gumustekin, Mukaddes; Erdal, Esra; Atabey, Nese
Graphical abstract: Highlights: Heparin increases TXNIP expression in HCC cells through: ChoRE-b on TXNIP promoter, nuclear accumulation of ChREBP/MondoA-Mlx, regulation of histon methyl-transferase EZH2, and histone modifications. TXNIP overexpression decreases adhesion and proliferation, where as increases migration and invasion ability of HCC cells. Heparin increases TXNIP expression in liver of diabetic rat. Abstract: Heparins play an important role in cell growth, differentiation, migration and invasion. However, the molecular mechanisms of heparin mediated cellular behaviors are not well defined. To determine the effect of heparin on gene expression, we performed a cDNA microarray in a hepatocellular carcinoma cell line and found that heparin regulates transcription of genes involved in glucose metabolism. In this study, we showed a new role of heparin in the regulation of thioredoxin interacting protein, which is a major regulator of glucose metabolism, in hepatocellular carcinoma cell lines. We determined the importance of a unique carbohydrate response element located on its promoter for the heparin-induced activation of thioredoxin-interacting protein and the modulatory role of heparin on nuclear accumulation of carbohydrate response element associated proteins. We showed the importance of heparin mediated histone modifications and down-regulation of Enhancer of zeste 2 polycomb repressive complex 2 expression for heparin mediated overexpression of thioredoxin-interacting protein. When we tested biological significance of these data; we observed that cells overexpressing thioredoxin-interacting protein are less adhesive and proliferative, however they have a higher migration and invasion ability. Interestingly, heparin treatment increased thioredoxin-interacting protein expression in liver of diabetic rats. In conclusion, our results show that heparin activates thioredoxin-interacting protein expression in liver and hepatocellular carcinoma cells and provide the first evidences of regulatory roles of heparin on carbohydrate response element associated factors. This study will contribute future understanding of the effect of heparin on glucose metabolism and glucose independent overexpression of thioredoxin-interacting protein during hepatocarcinogenesis.